Litter Decomposition of a Deciduous Tectona philippinensis and an Evergreen Parashorea malaanonan Across Contrasting Sites - Hernandez, Jonathan Ogayon; Maldia, Lerma San Jose; Tinio, Crusty Estoque; Combalicer, Marilyn Sabalvaro (Jurnal Sylva Lestari, 2024)
Litter traits and site conditions alter nutrient inputs from deciduous and evergreen forests by influencing litter decomposition processes. Here, we investigated the leaf and stem mass loss rate (MLR) of a deciduous (Tectona philippinensis) and an evergreen (Parashorea malaanonan) tree species and the factors influencing it through an intersite experiment and litterbag method in secondary forests in Lobo, Batangas and Mount Makiling Forest Reserve (MMFR). Variations in initial litter quality (leaf area, specific leaf area (SLA), leaf thickness, vein density), and site factors (light intensity and temperature) were assessed. P. malaanonan has a lower SLA and vein density than T. philippinensis. The leaf and stem MLR were significantly higher in the mixed litter (44.09–57.83%) than that of a single-species litter of either T. philippinensis (28.16–41.83%) or P. malaanonan (33.60–47.66%). The leaf MLR of T. philippinensis was greater when placed in Lobo (where the litter originated) than at a different site (i.e., MMFR). Moreover, leaf litter decomposition was faster in T. philippinensis than in P. malaanonan, particularly during the rainy season. Overall, the study showed that litter decomposition in deciduous and evergreen differed across sites due to variations in litter quality and environmental variables. Keywords: decomposability traits, home-field advantage (HFA), intersite experiment, litter quality, mass loss rate